2013
DOI: 10.1186/1756-0500-6-501
|View full text |Cite
|
Sign up to set email alerts
|

Concha bullosa mucocele with orbital invasion and secondary frontal sinusitis: a case report

Abstract: BackgroundAlthough concha bullosa (CB) is the most common variants of the middle turbinate, mucocele of CB is uncommon. Furthermore, CB mucocele with orbital invasion and secondary frontal sinusitis has not been reported previously.Case presentationA 42-year-old Korean male presented with gradually progressive proptosis of right eye and right-sided frontal headache. He had previously undergone endoscopic sinus surgery (ESS) 15 and 9 years ago. The endoscopic examination showed an expansive, large middle turbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…12,13 However, for CBMs, a cause-effect mechanism is not yet clear. Previous studies indicate either a mechanical (history of trauma, surgery, nasal polyposis, or benign tumors) or an inflammatory etiology (infection, allergy, cystic fibrosis), 5,8,12,14 whereas others did not support the obstructive causes of mucoceles. 14 …”
Section: Discussionmentioning
confidence: 95%
“…12,13 However, for CBMs, a cause-effect mechanism is not yet clear. Previous studies indicate either a mechanical (history of trauma, surgery, nasal polyposis, or benign tumors) or an inflammatory etiology (infection, allergy, cystic fibrosis), 5,8,12,14 whereas others did not support the obstructive causes of mucoceles. 14 …”
Section: Discussionmentioning
confidence: 95%
“…Lee et al, Yasan et al, and Armengot et al also reported similar findings in their case studies that CB mucocele/pyocele cause ipsilateral sinusitis. 3,18,23 Aktas D et al studied the CT paranasal scans of 54 patients with CB and found no relationship between unilateral and bilateral CB with sinusitis. 24…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rates for pneumatization of the MT is between 13 and 53.6%. [1][2][3][4] Concha bullosa is generally asymptomatic and diagnosed incidentally by computed tomography. Sometimes, an over-pneumatized MT can lead to nasal obstruction, contact headache, deviated nasal septum and chronic sinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…CB is the pneumatization of the MT and is one of the most common variations of the sinonasal anatomy. Pneumatization of the MT happens due to variation in the ethmoidal air cell system development (27)(28)(29). The CB turns into apparent after 7-8 years of age and continues its development even after the period of adolescence.…”
Section: Discussionmentioning
confidence: 99%